2002
DOI: 10.1093/humrep/17.8.2027
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and neonatal outcome after controlled ovarian stimulation for IVF using the GnRH antagonist ganirelix

Abstract: Reviewing the presented data and the literature on obstetric and neonatal outcome after conventional IVF or ICSI, we conclude that a controlled ovarian stimulation protocol including the novel GnRH antagonist ganirelix has been shown to be safe for pregnant women and their newborn babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…To the best of our knowledge, there has been no report of inadvertent use of GnRH antagonist in pregnancy. However, there are three reports of congenital malformations following IVF cycles with GnRH antagonists (78)(79)(80). The cause-effect relationship is unclear.…”
Section: Gonadotropin Releasing Hormone Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there has been no report of inadvertent use of GnRH antagonist in pregnancy. However, there are three reports of congenital malformations following IVF cycles with GnRH antagonists (78)(79)(80). The cause-effect relationship is unclear.…”
Section: Gonadotropin Releasing Hormone Antagonistsmentioning
confidence: 99%
“…Five newborns had minor congenital malformations (6.8%), and one had a major congenital malformation (1.4%). In another study, Boerrigter et al (80) reported the outcome of 424 children born following IVF cycles using ganirelix. The congenital malformation rate was 7.5% (32 of 424 children), similar to that observed in children born following GnRH agonist IVF cycles (5.5%, 10 of 181 children).…”
Section: Gonadotropin Releasing Hormone Antagonistsmentioning
confidence: 99%
“…Boerrigter et al [111] conducted a pooled analysis of all follow-up data of the phase 2 and 3 trials for the development of ganirelix. Data on 340 ongoing pregnancies and neonatal outcomes for 432 children showed that there were no differences between the GnRH antagonist and GnRH agonist regimens with respect to pregnancy loss after 16 weeks’ gestation, and the incidence and nature of complications during pregnancy and delivery did not differ between the two groups [111].…”
Section: Introductionmentioning
confidence: 99%
“…Data on 340 ongoing pregnancies and neonatal outcomes for 432 children showed that there were no differences between the GnRH antagonist and GnRH agonist regimens with respect to pregnancy loss after 16 weeks’ gestation, and the incidence and nature of complications during pregnancy and delivery did not differ between the two groups [111]. No major differences were observed in neonatal characteristics of infants in the ganirelix and agonist groups, who had an overall mean birth weight on average of 3200 g for singletons, 2300 g for twins, and 1800–1900 g for triplets.…”
Section: Introductionmentioning
confidence: 99%
“…After introduction of GnRH antagonist into clinical practice, it reduced OHSS rate in IVF/ICSI cycles (9). GnRH antagonist can improve the poor response to ovulation stimulation (6, 10, 11). Although many studies showed the benefits of GnRH antagonist on IVF/ICSI cycle outcomes but its effect is controversial.…”
Section: Introductionmentioning
confidence: 99%